Review of long-term immunogenicity following HPV vaccination: Gaps in current knowledge - J. Hoes; H. Pasmans; T. M. Schurink-van 't Klooster; F. R. M. van der Klis; R. Donken; J. Berkhof; H. E. de Melker (Taylor & Francis Group, 2022)
The licensed HPV vaccines are highly efficacious and induce high levels of neutralizing antibody levels, the assumed mediators of protection. However, a correlate of protection against HPV is lacking, and the evidence is still limited as to long-term persistence of antibodies, especially following reduced dosing schedules. The World Health Organization (WHO) urges immunization of young girls as part of the strategy to eliminate cervical cancer, thus long-lasting protection is required. The current review describes long-term follow-up regarding vaccine-induced seropositivity and antibody level development following the different vaccines and dosing schedules. Implications and opportunities of long-term vaccine-induced immune responses are discussed, such as the gaps in monitoring of long-term immunogenicity, the possibilities of reduced dosing schedules, and the importance of evidence for durable immunity.